Study on the Catalytic Activity of Cerium/Cadmuim Mixed Oxide Catalysts for the Photo catalytic Degradation of Orange G Dye - Alwash, Atheel (Al-Nahrain Journal for Engineering Sciences, 2017)
The Mono and binary-mixed oxide catalysts were prepared by precipitation and co-precipitation method and investigated for the photocatalytic decolorization of orange G dye which was used as a pollutant model in this study. The structure of the synthesized catalysts were characterized by the X-ray diffraction (XRD), bonding by fourier transfer infrared (FTIR), morphology by scanning electron microscope (SEM) and reflection using UV-VIS diffuse reflectance spectra. The XRD results revealed that the mono oxide catalysts confirm well the cubic phase of cadmium and cerium oxide and that their mixed oxide catalyst i.e. 50Ce/25Cd show the same characteristic peaks of pure cerium oxide with slight shift to higher wave lengths for two crystalline peaks at 33.15° and 56.15° respectively. The FTIR spectra of 50Ce/25Cd mixed oxide catalyst improved the combination between both pure cadmium and cerium oxide catalyst. The diffuse reflectance showed a blue shift towards lower wave length and that the energy gap was increased with an increase in cerium content. Different reaction variables such as, effect of metal content, pH values, amount of hydrogen peroxide and effect of catalyst amount were studied to estimate their effect on the decolorization efficiency of orange G dye. The maximum catalytic activity achieved was 91% at a solution pH of 2.1, catalyst dosage of 1.5 g/L, 0.15 mL of H2O2 /100 mL of reaction volume and initial dye concentration of 10 mg/L after 60 min of reaction time.